Altered Mental Status Among Febrile Hospitalized HIV-Infected Children Aged 0–59 Months in Mozambique. (10th August 2020) - Moon, Troy D; Maússe, Fabião E; Gebretsadik, Tebeb; Kenga, Darlenne B; Charles, Pedro; Agy, Mustuafá; Simbine, Samuel; Sacarlal, Jahit
Abstract: Background: Altered mental status (AMS) is a priority presenting sign that must be assessed in HIV-infected, febrile children, yet diagnosis is difficult in areas with limited diagnostic capacity. Malaria and bacterial meningitis have been reported as the most common causes of AMS in febrile children presenting to the hospital in sub-Saharan Africa. However, in an HIV-infected child, central nervous system manifestations are diverse. Methods: We conducted a clinical observational study of HIV-infected febrile children, aged 0–59 months, hospitalized in Mozambique and prospectively followed. Within this cohort, a nested study was designed to characterize children admitted with AMS and to assess factors associated with mortality. Univariate and multivariable analysis were performed comparing characteristics of the cohort by AMS status and evaluated demographic and clinical factors by in-hospital mortality outcome. Results: In total, 727 children were enrolled between April 2016 and February 2019, 16% had AMS at admission. HIV-infected, febrile children, who presented with AMS and who had a diagnosis of bacteremia, had a 4-fold increased relative odds of in-hospital mortality, and children who presented with neurologic symptoms on admission had a roughly 8-fold higher odds of in-hospital mortality relative to children without presenting neurologic findings. Conclusions: Mozambique has a pressing need to expand local diagnostic capacity. Our results highlight the critical need for clinicians to incorporate a broader differential into their potential causes of AMS, and to develop a Ministry of Health approved diagnostic and management algorithm, which is standardly used, to manage patients for whom reliable and relevant diagnostic services are not available.